1989
DOI: 10.1104/pp.91.2.451
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation is Reduced in DNasel-Sensitive Regions of Plant Chromatin

Abstract: Pea, barley, and com chromatin was isolated and subjected to limited digestion with DNasel. The preferentially degraded, small molecular weight fraction, presumably consisting of sequences in an active state of expression, was isolated and its 5-methylcytosine content determined. The DNasel-sensitive chromatin fraction from all three plant species investigated contained a markedly reduced level of DNA methylation compared to total DNA.The DNA of higher animals and plants contains the modified base m5C4 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Subsequent studies, however, found a close correlation between chromatin structure and transcriptional activity, and characteristic dierences in chromatin structure among dierent tissues (Baluska 1990). DNase I accessibility studies showed that DNase I-sensitive regions of plant chromatin showed markedly reduced DNA methylation (Klaas and Amasino 1989), and demonstrated a generally open chromatin structure for transgenes (Weising et al 1990) and endogenous genes (Conconi and Ryan 1993) that was independent of the transcriptional activity of the genes.…”
Section: Introductionmentioning
confidence: 96%
“…Subsequent studies, however, found a close correlation between chromatin structure and transcriptional activity, and characteristic dierences in chromatin structure among dierent tissues (Baluska 1990). DNase I accessibility studies showed that DNase I-sensitive regions of plant chromatin showed markedly reduced DNA methylation (Klaas and Amasino 1989), and demonstrated a generally open chromatin structure for transgenes (Weising et al 1990) and endogenous genes (Conconi and Ryan 1993) that was independent of the transcriptional activity of the genes.…”
Section: Introductionmentioning
confidence: 96%
“…[ [33][34][35][36] The latter is not a preferred option due to the potential of contamination from 5-methylcytosine derived from RNA that maybe present in the DNA sample which is also released by acid hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…DNasel-sensitive regions are undermethylated relative to total plant DNA (Klaas and Amasino, 1989) but methylation patterns do not necessarily change with modifications of chromatin accessibility. Appearance of DNaseI-hypersensitive sites in the maize Adhl gene (Nick et al, 1986) and a pea rbcS gene (Goerz et al, 1988) after induction was not accompanied by changes in DNA methylation.…”
Section: The Role Of Dna Methylation In Chromatin-mediated Gene ~Egulmentioning
confidence: 98%